2013
DOI: 10.1021/ar300337f
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Controlled Oligocholate Membrane Transporters: Learning through Water Play

Abstract: Controlled translocation of molecules and ions across lipid membranes is the basis of numerous biological functions. Because synthetic systems can help researchers understand the more complex biological ones, many chemists have developed synthetic mimics of biological transporters. Both systems need to deal with similar fundamental challenges. In addition to providing mechanistic insights into transport mechanisms, synthetic transporters are useful in a number of applications including separation, sensing, dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 69 publications
0
52
0
Order By: Relevance
“…Consequently, the hydrophobic-hydrophilic balance of the compound is either increased or reduced, thus modifying its self-aggregation in aqueous solution. Several papers dealing with the physicochemical properties and applications in fields such as supramolecular chemistry, biomedicine, and pharmaceutics have been reported [18,[22][23][24][25][26][27][28].…”
Section: R1mentioning
confidence: 99%
“…Consequently, the hydrophobic-hydrophilic balance of the compound is either increased or reduced, thus modifying its self-aggregation in aqueous solution. Several papers dealing with the physicochemical properties and applications in fields such as supramolecular chemistry, biomedicine, and pharmaceutics have been reported [18,[22][23][24][25][26][27][28].…”
Section: R1mentioning
confidence: 99%
“…[21] Charged functional groups (e.g., ammonium, guanidinium, or carboxylate) often have a strong tendency to stay within or at least close to water to satisfy their solvation needs. [22] Binding selectivity of MINP-COOH An important property of molecularly imprinted materials is their binding selectivity. The above study demonstrated binding selectivity for acid-and base-functionalized template analogues in a pH-dependent manner.…”
Section: Characterization Of the Carboxylic Acid-containing Binding Pmentioning
confidence: 99%
“…16−20 This Feature Article summarizes our recent efforts in polymerizing/cross-linking surfactant micelles and converting them into multifunctional nanoparticles. Our surface-cross-linked micelles (SCMs) can be tuned in multiple ways including surface functionality, internal content, and water or oil solubility.…”
Section: Introductionmentioning
confidence: 99%